Test-retest and inter-monitor reliability of the Atlas activity monitor for assessing resistance training exercises - Montoye, A. H.; Conger, S. A.; Mitrzyk, J. R.; Beach, C.; Fox, A. K.; Steeves, J. A. (Journal for the Measurement of Physical Behaviour, 2019)
Background: Resistance training (RT) is an integral component of physical activity guidelines, but methods for the objective assessment of RT have been limited. Recently, the Atlas Wearables Wristband2 has been marketed to measure RT, but its reliability is unknown. Purpose: To determine the reliability of the Wristband2 for measuring RT exercises. Methods: Participants (n = 62) aged 18-52 yrs. wore two Wristband2 monitors on the left wrist and performed 2 sets of 12 repetitions of 14 different resistance training exercises. Test-retest reliability was determined by calculating percent agreement for exercise type and for repetitions recorded by a single Wristband2 between sets 1 and 2 for each exercise, and inter-monitor reliability was determined by calculating percent agreement for exercise type and for repetitions recorded by both Wristband2 monitors in set 1 of each exercise. Results: Test-retest reliability for exercise type was 80.0 ± 1.0% (lowest: 69.4% for bench press; highest: 95.2% for biceps curls) and for repetition count was 47.9 ± 2.2% (lowest: 19.4% for calf raises; highest: 82.3% for lateral raises). Inter-monitor reliability for exercise type was 80.4 ± 1.3% (lowest: 66.1% for bench press; highest: 95.2% for biceps curls) and for repetition count was 59.6 ± 2.2% (lowest: 32.3% for calf raises; highest: 88.7% for lateral raises). Subgroup analyses by gender, RT experience, and participant height revealed minimal differences in reliability. Repetition agreement of =1 repetition increased test-retest reliability to 74.7% and inter-monitor reliability to 83.7%. Conclusion: The Wristband2 had acceptable test-retest and inter-monitor reliability for the majority of exercises tested and for counting repetitions to within 1 repetition/set.